"As a clinician, you have to be passionately involved": Advocacy and professional responsibility in gender-affirming healthcare. (March 2023) - Lynne-Joseph, Alyssa
Abstract: Previous research has studied how clinicians such as physicians, nurses, social workers, and nutritionists understand advocacy as a professional responsibility. Analyses have typically focused on individual healthcare professions and have viewed ambiguity around the conceptualization of advocacy as detrimental. Little research has considered how multiple professions within a single field of healthcare interpret clinician advocacy, nor how ambiguity might be productive in a multidisciplinary field. This article addresses these gaps by utilizing science and technology studies scholarship on buzzwords to analyze how clinicians in the field of gender-affirming healthcare have come to understand advocacy as a professional responsibility despite significant ambiguity around the goals, tactics, and targets of advocacy. Gender-affirming healthcare refers to any kind of physical or mental healthcare that transgender and gender diverse (TGD) people obtain to affirm their gender identity. Drawing on interviews with 30 U.S. clinicians, observation of nine transgender health conferences, and content analysis of 202 professional journal articles and 11 professional association statements, I argue that ambiguity around advocacy has been key to its uptake as a responsibility across multiple professions in this field. Foregrounding interview data, I show how polysemy allows clinician respondents across professions to reassert their expertise as they delineate what constitutes good gender-affirming healthcare and defend the emergent field in three problem domains: health insurance, the marginalization of TGD people, and the legality of gender-affirming healthcare. I also demonstrate how theoretical work on buzzwords explains why three clinician respondents rejected advocacy as a professional responsibility. Highlights: Many clinician respondents view advocacy as a professional responsibility. Advocacy's conceptual ambiguity allows flexibility in its uptake by respondents. Diverse interpretations of advocacy are used to delineate what is "good" care. Respondents use advocacy to defend gender-affirming healthcare as a field. Clinician respondents' interpretations of advocacy span professional boundaries.